Pronunciation Strategies use by BIPA Teachers - Siswanti, Denti; Syafryadin (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
This study investigates the pronunciation strategies used by Bahasa Indonesia bagi Penutur Asing (BIPA) teachers to improve their students' phonetic proficiency. There were twenty-eight teacherssurveyed and interviewed as part of a qualitative-methods strategy to gather data. The results show that teachers use a range of strategies to students to helph typical pronunciation issues, including drilling, repetition, using the native speakers audio, the direct method, visual audio, etc. Teachers say using these strategies helps students pronounce words correctly and boosts their confidence when speaking Indonesian. Disparities in student competency and a lack of resources were noted as barriers to successful adoption, nevertheless.According to teachers, incorporating these techniques greatly enhances pupils' confidence when speaking Indonesian and helps them pronounce words correctly. However, obstacles to successful implementation were identified, including disparities in student competency and a lack of resources. The study ends with suggestions for creating focused training courses for BIPA teachers to improve their teaching methods and raise pronunciation proficiency among students. These revelations advance our knowledge of successful language teaching strategies in multilingual settings.